Comic Strip Design as an Alternative Learning Media in Disaster Themes for Elementary Students - Muhammad Radhi Zakaria; Nazli Ismail*; Hamdani Muhammad Syam; Marlina Marzuki; Manovri Yeni (Universitas Syiah Kuala, 2023)
Most children are interested in comics so that the media has the potential to be used in the learning and teaching process at school. We have developed and implemented comic strips for learning related to disasters in the fifth-grade science subject at SD Negeri Buengcala, Aceh Besar District. The designed materials were validated by experts and the attractiveness of the comic media was measured based on class observation during teaching and learning proceses related to students’ involvement and responses through the questionnaires. Quantitaively the questionnaries were scored (1 to 4) from too bad to very interested. The experts concluded that the media are valid with unrevised criteria including the attractiveness of media and language used. Based on the questionnaires, the students also agreed that the class was very interested. Therefore, the comic strip media can be developed potentially for disaster education at elementary schools